Book review: Digital literacy, inclusivity and sustainable development in Africa - Elena Maceviciute (Information Research: An International Electronic Journal)
Asamoah-Hassan, Helena (ed.). Digital literacy, inclusivity and sustainable development in Africa. London: Facet Publishing, 2022. xviii, 237 p. ISBN 978-1-78330-511-7